Water quality and irrigation suitability of freshwater lakes in Sudurpaschim Province, Nepal: A case study of Alital and Bandatal - Dahal, Bindu; Adhikari, Bikram; Prasai Joshi, Tista; Sharma, Motee Lal; Awasthi, Mahesh Prasad; Joshi, Kamana; Kafle, Jeevan; Pant, Ramesh Raj (Scientific World, 2025)
Water quality is an increasing concern globally due to climate change, rapid population growth, expanding industrial activities and intensive agricultural practices. This study evaluates the drinking water quality and irrigation suitability of Alital and Bandatal in the Sudurpaschim Province, Nepal, emphasizing their significance for local livelihoods and ecosystem sustainability. A comprehensive assessment was conducted using the Water Quality Index (WQI) and several irrigation-related parameters, including EC, SAR, PI, MAR, Na%, PS, CROSS, and RSBC. Results indicate that both the wetlands possess excellent irrigation potential, although moderate salinity was observed in some Bandatal samples. Based on EC and SAR correlations, Alital water was classified as C1S1, while Bandatal exhibited both C1S1 and C2S1 types. WQI values further confirmed excellent water quality, with scores of 8.61 ± 0.99 for Alital and 12.62 ± 3.62 for Bandatal, both within drinking water quality standards. These findings highlight the high water quality and irrigation suitability of the lakes, while also underscoring the need for ongoing monitoring in light of increasing urbanization and climate change pressures on these vital freshwater resources.